Curd As a Substitute to Cream Cheese in Making Japanese Cotton Cake - Nisak, Khairun (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2022)
The purpose of this research is to see if curd can be used as an ingredient to replace cream cheese in the production of Japanese cotton cakes. This study was carried out at the Yogyakarta AMPTA Tourism College's Pastry Laboratory. This is a quantitative study using an experimental method. Data collection methods utilizing a questionnaire / questionnaire technique Purposive sampling was used to collect research data from the distribution of questionnaires to 18 specific respondents. The descriptive quantitative data analysis method was used to determine the average value of food quality indicators. The collected data was then processed with the IBM SPSS Statistics 20 program. The analysis of consumer response data on the level of similarity in product quality of Japanese cotton cake curd and the original Japanese cotton cake yielded the highest average level of similarity in product quality on the taste indicators, with each value of 3.78 for sweet taste and 3.72 for savory taste. The color indicator, both the surface and inner color of the cake, comes in second with an average of 3.67. The average value of the typical aroma indicator is 3.61 in the third order. The average of the four indicators of the appearance of the cake surface is 3.56. The fifth texture indicator order, with an average value of 3.28. Kelima nilai ini memiliki nilai rata-rata 3 dari maksimal nilai 4.